Unbroken eaudiobook A world war ii story of survival, resilience, and redemption. - Hillenbrand, Laura (Random House Audio, 2010)
#1 NEW YORK TIMES BESTSELLER • The incredible true story of survival and salvation that is the basis for two major motion pictures: Unbroken and Unbroken: Path to Redemption . “Extraordinarily moving . . . a powerfully drawn survival epic.”— The Wall Street Journal Hailed as the top nonfiction book of the year by Time magazine • Winner of the Los Angeles Times Book Prize for biography On a May afternoon in 1943, an Army Air Forces bomber crashed into the Pacific Ocean and disappeared, leaving only a spray of debris and a slick of oil, gasoline, and blood. Then, on the ocean surface, a face appeared. It was that of a young lieutenant, the plane’s bombardier, who was struggling to a life raft and pulling himself aboard. So began one of the most extraordinary odysseys of the Second World War. The lieutenant’s name was Louis Zamperini. In boyhood, he’d been a cunning and incorrigible delinquent, breaking into houses, brawling, and fleeing his home to ride the rails. As a teenager, he had channeled his defiance into running, discovering a prodigious talent that had carried him to the Berlin Olympics and within sight of the four-minute mile. But when war had come, the athlete had become an airman, embarking on a journey that led to his doomed flight, a tiny raft, and a drift into the unknown. Ahead of Zamperini lay thousands of miles of open ocean, leaping sharks, a foundering raft, thirst and starvation, enemy aircraft, and, beyond, a trial even greater. Driven to the limits of endurance, Zamperini would answer desperation with ingenuity; suffering with hope, resolve, and humor; brutality with rebellion. His fate, whether triumph or tragedy, would be suspended on the fraying wire of his will. Laura Hillenbrand writes with the same rich and vivid narrative voice she displayed in Seabiscuit . Telling an unforgettable story of a man’s journey into extremity, Unbroken is a testament to the resilience of the human mind, body, and spirit.